Influence of oil type on acrylamide formation in intermittent fried beef nuggets and in asparagine-glucoselipid system - Ahmad, Siti Nur Syahirah (2021)
This study aims to investigate the effect of different vegetable oils and frying cycles on acrylamide formation during the intermittent frying of beef nuggets. Different vegetable oils, palm olein (PO), red palm super olein (RPSO), sunflower oil (SFO), and soybean oil (SBO), were used for a total of 80 frying cycles. Oil was collected at every 16th frying cycle and analysed for peroxide value (PV), panisidine value (p-AV), free fatty acid (FFA), total polar compound (TPC), polar compound fractions, and fatty acid composition (FAC). Total oxidation (TOTOX) value was calculated, and acrylamide content was quantified in the nuggets. Regardless of the oil type, PV, p-AV, and TOTOX initially increased but gradually decreased. However, FFA and TPC continued to develop across the 80 frying cycles. The C18:2/C16:0 remained almost unchanged in PO and RPSO but dropped progressively in SFO and SBO. The lowest acrylamide content in fried products was observed in the PO, while the highest content was observed in RPSO. The oil type but not the frying cycle significantly affected the acrylamide concentration in beef nuggets. PO is shown to be the most suitable vegetable oil to be used in lowering acrylamide formation during heat treatment. Next, the effect of different compositions of beta-carotene and vitamin E in RPSO blends on the kinetics parameters of acrylamide formation/elimination in an asparagineglucose- lipid model system. Different blends of RPSO and canola oil (10, 20 and 30%) were applied and heated at series of temperature (120, 140, 160, 180, and 200°C) for 20 min. Linear equation for each oil blend was plotted in which the activation energy (Ea) was estimated and found that acrylamide formation obeyed the Arhenius Law. Higher level of RPSO incorporated in the blend led to a higher amount of beta carotene and tocols in the blend. Acrylamide content was determined using GCMS method and results indicated that the acrylamide formation obeyed the Arrhenius Law. Highest acrylamide content was revealed when 30% RPSO used at temperature 200°C whereas the lowest was noted when 20% RPSO was used at 120°C. Per contra for Ea which 20% RPSO revealed the highest and 30% RPSO the lowest revealing that higher energy was required for the reaction to proceed then leading to lower acrylamide formation compared to others. The kinetics parameters of different oil blends of RPSO estimated in the present study may provide insight into the optimum RPSO blend to reduce acrylamide formation during heat treatment.